Penentuan Komponen Flavor Kopi Luwak Robusta Artifisial Melalui Analisis Sensoris dan Gas Chromatography-Mass Spectometry (GCMS) - Ikhwan Samsul Hadi Sidiq; Mukhammad Fauzi (Jurnal Teknologi dan Mutu Pangan, 2026)
The high demand for civet coffee has led to the over exploitation of civets. The in vitro fermentation process aims to artificially mimic the enzymatic processes of the civet’s digestive system. This study aims to produce artificial Robusta civet coffee with sensory characteristics and flavor components similar to those of civet coffee. The method used was a factorial Complete Randomized Design with treatments consisting of civet feces yeast (B1) and a combination of α-amylase enzyme and civet feces yeast (B2). Fermentation times were set at intervals of 8 hours (A1), 16 hours (A2), 24 hours (A3), and 32 hours (A4). The results showed that the best treatment for the overall cupping test score was the combination of α-amylase and dried yeast at an 8-hour fermentation time (A1B2), which scored 8.13 (excellent). Additionally, the analysis using Gas Chromatography-Mass Spectrometry (GC-MS) analysis revealed major flavor components such as furan (28.28%), pyridine (8.98%), pyrazine (9.98%), benzene (9.02%), organic acids (3.48%), and alcohols (3.84%). Therefore, the conclusion of this study is that the addition of α-amylase and yeast during an 8-hour fermentation process has the potential to serve as an alternative to artificial Robusta civet coffee that mimics natural civet coffee without involving civet animals. It is hoped that this research can serve as a foundation for coffee development in the community.